Regional differences in technical efficiency and technological gap of Norwegian dairy farms: a stochastic meta-frontier model. Issue 4 (20th January 2019) - Alem, Habtamu; Lien, Gudbrand; Hardaker, J. Brian; Guttormsen, Atle
ABSTRACT: This paper compares technical efficiencies (TEs) and technological gap ratios (TGRs) for dairy farms in regions of Norway, accounting for differences in working environments. We used the state-of-the-art stochastic meta-frontier approach to estimate TEs and TGRs to account for regional heterogeneity, and the 'true' random-effect model to account for farm effects. The dataset used was farm-level balanced panel data for 24 years (1992–2014), with 5442 observations from 731 dairy farms. The results of the analysis provide empirical evidence of small regional differences in TEs, TGRs, and input use. Furthermore, the results may provide support for the more regionally specific agricultural policy, in terms of support schemes and structural regulations.